THE IMPACT OF SEAPORT CARGO ON ECONOMIC DEVELOPMENT: PANEL DATA EVIDENCE FROM TÜRKIYE - Tehci, Ali; Selamzade, Fuad; Demirkol, Sam; Kama, Aycan; Ersoy, Yusuf (Univ Dubrovnik, 2025)
The strategic importance of ports increases the share of maritime transport in international trade. Most of the cargo handled in ports is related to foreign trade. The current study focuses on the impact of the outputs of 18 container and cargo ports involved in international trade in T & uuml;rkiye on macroeconomic indicators. The effects of the cargo outputs of the ports for the years 2004-2022 on GDP were estimated using panel data regression models. The results show that the amount of cargo handled in ports influences the exports and industrial production of the provinces. It was also concluded that the amount of cargo exports has an essential impact on increasing GDP. It is imperative to enhance ports and fully utilize their potential.
Keywords: Maritime Transportation; Port; Economic Development; Gdp; Panel Data Regression